Implementasi Program Desa Vokasi di Kota Semarang - Adib Afdholi; Aufarul Marom; Fathurrohman Fathurrohman (Journal of Public Policy and Management Review, 2015)
Village vocational program is a program that is published by the government in efforts to reduce poverty by providing training to the public in accordance with the existing potential region. Village vocational programs in Semarang has been implemented starting in 2009 conducted by the Education Department of Semarang with a number of activities until the year 2013 amounted to 70 activities in 14 villages. Vocational Education Research Program Implementation village in Semarang is motivated still high levels of poverty in the city of Semarang. This study used qualitative research methods. The sample in this research were taken from three villages in Semarang namely in Wonolopo Village, Village Jomblang and Village Plombokan with each village used samples of 2 activities. Analysis of data using evalusai the performance of activities in accordance with the reporting guidelines for preparation of the government accountability. The phenomenon of research in the form of the factors that affect the implementation, achievement of the respective program of activities and constraints experienced in the implementation of the program. Implementation Program of Vocational Village in Semarang, there are two factors that affect the implementation of that factor and the role of inter-organizational coordination and program resources. Village of Vocational Achievement Program in Semarang for 95,525% and according to the statutes assessment program results are at levels very successful. Obstacles in the implementation of the program is the lack of capital to run the program after the training, the difficulty of marketing, lack of commitment from members continue to pioneer training results and error nature uasaha election activities. Advice given is, (1) Should the budget for business capital so it can be improved; (2) The assistance to the group after training; (3) Selected activities should be able to be observed again adapted to the conditions that exist in the community, the environment in the community, and the interests of society.